Walleye Autochthonous Bacteria as Promising Probiotic Candidates against Flavobacterium columnare - Seghouani, Hamza; Garcia-Rangel, Carlos-Enrique; Füller, Jérémie; Gauthier, Jeff; Derome, Nicolas (Frontiers in Microbiology, 2017)
Walleye (Sander vitreus) is the second most fished freshwater species in Canada. While much sought by anglers, walleye also supports substantial commercial fisheries. To cope with the recent decline of wild walleye populations, fish farmers produce juveniles for lake stocking. However, walleye breeding is particularly tedious, mostly due to high disease susceptibility at larval and juvenile developmental stages. The main threat is the columnaris disease, which is caused by Flavobacterium columnare, an opportunistic bacteria. As F. columnare strains exhibit increasing antibiotic resistance, there is a strong need to develop efficient and sustainable alternative strategies to control columnaris disease. Bacterial probiotics have been shown to mitigate infections either by enhancing host immune response or by inhibiting pathogen growth. Being successfully assessed in many fish/pathogen combinations, we developed a tailored probiotic strategy for walleye to prevent and treat columnaris disease. Thirty-seven endogenous bacterial strains were isolated from healthy walleye’s skin and gut, were tested in vitro against F. columnare. Significant antagonistic effect against F. columare was measured for two out of thirty-seven endogenous strains. These two probiotic strains were identified as Pseudomonas fluorescens. The antagonistic effect of these two successful probiotics was further validated in vivo during a two months stress trial: groups receiving probiotic treatments showed on average 53.74% survival improvement